Proceedings of the Fourteenth Annual ACM-SIAM Symposium on Discrete Algorithms 2020
DOI: 10.1137/1.9781611975994.63
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Polynomial Algorithms for Submodular Tree Orienteering and Other Directed Network Design Problems

Abstract: We consider the following general network design problem on directed graphs. The input is an asymmetric metric (V, c), root r * ∈ V , monotone submodular function f : 2 V → R + and budget B. The goal is to find an r * -rooted arborescence T of cost at most B that maximizes f (T ). Our main result is a simple quasi-polynomial time O( log k log log k )-approximation algorithm for this problem, where k ≤ |V | is the number of vertices in an optimal solution. To the best of our knowledge, this is the first non-tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Grandoni, Laekhanukit, and Li [8] recently gave a tight quasi-polynomial time O(log 2 k/ log log k)-approximation for the Directed Steiner Tree problem, based on the Sherali-Adams hierarchy. Later, Ghuge and Nagarajan [6] showed that the same result can be obtained using a combinatorial algorithm, based on guessing what happens in the optimum directed Steiner tree. The guess-and-divide framework was also used in a recent result of Lokshtanov et al [11] to obtain a tight 2-approximation for the feedback vertex set on tournament graphs in polynomial time.…”
Section: The Power Of Linear Programming Hierarchy Vs Guessingmentioning
confidence: 82%
“…Grandoni, Laekhanukit, and Li [8] recently gave a tight quasi-polynomial time O(log 2 k/ log log k)-approximation for the Directed Steiner Tree problem, based on the Sherali-Adams hierarchy. Later, Ghuge and Nagarajan [6] showed that the same result can be obtained using a combinatorial algorithm, based on guessing what happens in the optimum directed Steiner tree. The guess-and-divide framework was also used in a recent result of Lokshtanov et al [11] to obtain a tight 2-approximation for the feedback vertex set on tournament graphs in polynomial time.…”
Section: The Power Of Linear Programming Hierarchy Vs Guessingmentioning
confidence: 82%
“…In [27], an approximation algorithm is proposed that runs in quasi-polynomial time for the submodular tree orienteering problem. Differently from us, they work on directed graphs.…”
Section: Related Workmentioning
confidence: 99%
“…The goal is to maximize f (S). Currently, the best result for this setting is due to Kesselheim and Tönnis [20], who achieve a 1/e-competitive ratio in exponential time in k, or 1 e (1 − 1 e ) in polynomial time in n and k. Submodular functions also has been used in the network design problems [15,14]. There are also some related online coloring problems in the literature [16,1].…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, submodular optimization has found applications for different machine learning and data mining applications including data summarization, sparsity, active learning, recommendation, high-order graphical model inference, determinantal point processes [12,4,19], network inference, network design [15,13], and influence maximization in social networks [19].…”
Section: Introductionmentioning
confidence: 99%